Analisis Kontribusi dan Efektivitas Pajak Restoran Terhadap Pajak Daerah Kabupaten Tabalong - Fahrul Abadi; Chairul Sa’roni (PPJP Universitas Lambung Mangkurat, 2023)
The purpose of this study was to determine the growth rate of the Tabalong Regency restaurant tax, how much the restaurant tax contribution to the Tabalong Regency regional tax, and the aim to determine the Tabalong Regency restaurant tax's effectiveness. The data used in this study are secondary data and primary data using Time Series data from 2011 to 2019. The data source is obtained from the Tabalong Regency Regional Finance Agency. The method used is the descriptive quantitative method.Based on the research results, Tabalong Regency has as much as 25.88% for restaurant taxes; this is the less successful group. The calculation result is 24.33% for the restaurant tax contribution, including the contribution in Tabalong Regency. For the effectiveness, of the influential group because it obtained 117.20%